The Role of User Guidance in the Industrial Adoption of MDE Approach - Rauhamäki, Jari; Laitinen, Outi; Sierla, Seppo; Kuikka, Seppo (Electronic Communications of the EASST, 2011)
Model-Driven Engineering (MDE) has emerged as an actively researched and established approach for next generation control application development. Technology transfer to the industry is a topical research problem. Since most professional factory process control engineers do not have computer science backgrounds, there is an urgent need for studies of the role of user guidance in the professional learning, and thus, of industrial adoption of MDE approaches. In this study professionals were invited to a hands-on assessment of the AUKOTON MDE approach for factory process control engineering. Qualitative empirical material was collected and analyzed to identify the role of user guidance in the context of other factors impacting industrial adoption. Challenges in adoption that could be solved by user guidance were identified with the theory of organizational knowledge creation (SECI) model.